Gaya Kepemimpinan Yang Ideal Untuk Generasi Milineal - Riki Andi Saputro (Universitas Sebelas Maret, 2022)
Leadership is an ability or strength in a person to lead and influence others in terms of work, where the goal is to achieve predetermined goals. The development of today's era has influenced all aspects, including aspects of leadership style. In today's millennial generation, the challenge of having an ideal leader that fits the current era is very big. This study aims to see how the ideal leadership style. The focus of the research is to examine the ideal leadership style for the millennial generation. The method used in this research is literature study related to theory and references. The results of the research on the ideal leadership style for the millennial generation, namely effective government will be realized if the leader can meet the qualifications as a credible leader, has the ability, intellect, good vision and has integrity, honesty and loyalty to interests. from the community. Building a region that is led must have a foundation, namely independence and entrepreneurship that gives pleasure and satisfaction to the community. Leadership in the millennial era has a unique approach because digitalization that has penetrated the world of work no longer allows leaders to act conventionally.